A ladder coordination polymer based on Ca2+ and (4,5-dicyano-1,2-phenylene)bis(phosphonic acid): crystal structure and solution-state NMR study - Venkatramaiah, Nutalapati (2017)
The preparation of coordination polymers (CPs) based on either transition metal centres or rare-earth cations has grown considerably in recent decades. The different coordination chemistry of these metals allied to the use of a large variety of organic linkers has led to an amazing structural diversity. Most of these compounds are based on carboxylic acids or nitrogen-containing ligands. More recently, a wide range of molecules containing phosphonic acid groups have been reported. For the particular case of Ca2+-based CPs, some interesting functional materials have been reported. A novel one-dimensional Ca2+-based coordination polymer with a new organic linker, namely poly[[diaqua[mu(4)-(4,5-dicyano-1,2-phenylene) bis(phosphonato)][mu(3)-(4,5-dicyano-1,2-phenylene)bis(phosphonato)]dicalcium(II)] tetrahydrate], {[Ca-2(C8H4N2O6P2)(2)(H2O)(2)]center dot 4H(2)O}(n), has been prepared at ambient temperature. The crystal structure features one-dimensional ladder-like (1)(infinity)[Ca-2(H(2)cpp)(2)(H2O)(2)] polymers [H(2)cpp is (4,5-dicyano-1,2-phenylene) bis(phosphonate)], which are created by two distinct coordination modes of the anionic H(2)cpp(2-) cyanophosphonate organic linkers: while one molecule is only bound to Ca2+ cations via the phosphonate groups, the other establishes an extra single connection via a cyano group. Ladders close pack with water molecules through an extensive network of strong and highly directional O-H center dot center dot center dot O and O-H center dot center dot center dot N hydrogen bonds; the observed donor-acceptor distances range from 2.499 (5) to 3.004 (6) angstrom and the interaction angles were found in the range 135-178 degrees. One water molecule was found to be disordered over three distinct crystallographic positions. A detailed solution-state NMR study of the organic linker is also provided.